Magnetic Resonance Defecography in Obstructive Defecation Syndrome: A Pictorial Review Imaging Findings and Impact on Surgical Management - Sud, Seema; Khurana, Rishabh; Agarwal, Brij B.; Buxi, Tarvinder B.S.; Ghuman, Samarjit S. (Indographics, 2022)
Pelvic floor, a funnel-shaped muscular structure plays a significant role in bowel and bladder activities. Defecatory disorders result from the structural changes and functional disorders. Pelvic floor dysfunction affects 15% of multiparous women. It is being expected that after 30 years, there would be 45% rise in demand of pelvic floor imaging. After ruling out primary and secondary causes of constipation, diagnosis of obstructed defecation syndrome (ODS) is made. ODS is emerging as one of the important causes of constipation. As the symptoms are nonspecific and examination findings are frequently inaccurate, the clinical evaluation becomes a difficult task. Hence, various imaging modalities are becoming popular as an adjunct tool for the assessment of these disorders. Clinical management of ODS is based on the Constipation and Bowel Activity Score (CABA) and delineation of the pelvic floor anatomy. After defining the pelvic floor anatomy–based structural abnormality, day care ambulatory surgical procedure, that is, stapled transanal resection rectopexy (STARR), is offered to the patients of ODS. It provides significant relief to patients suffering from constipation and reduction in postoperative CABA score. This review discusses the role of magnetic resonance defecography imaging in ODS its impact on subsequent management.
Keywords: magnetic resonance defecography; obstructed defecation syndrome; constipation and bowel activity score